2009
DOI: 10.1093/eurheartj/ehp420
|View full text |Cite
|
Sign up to set email alerts
|

N-terminal pro-B-type natriuretic peptide is an independent predictor of cardiovascular morbidity and mortality in the general population

Abstract: In this large community-based cohort, plasma NT-proBNP was a strong predictor of death and a wide range of CV events.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
99
1
6

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 112 publications
(112 citation statements)
references
References 34 publications
6
99
1
6
Order By: Relevance
“…The PREVEND study has been described in detail elsewhere [15,16]. During the period 1997-1998, 8592 subjects were enrolled in the PREVEND cohort.…”
Section: Prevendmentioning
confidence: 99%
See 1 more Smart Citation
“…The PREVEND study has been described in detail elsewhere [15,16]. During the period 1997-1998, 8592 subjects were enrolled in the PREVEND cohort.…”
Section: Prevendmentioning
confidence: 99%
“…A C-reactive protein level >3 mg L )1 was defined as elevated. N-terminal pro-B-type natriuretic peptide (NTproBNP) (pg mL ) was measured as previously described [16]. UAE was calculated as the average value from two consecutive 24-h urine collections.…”
Section: Measurement Of Galectin-3mentioning
confidence: 99%
“…Indeed some clinical guidelines have started to recommend testing for such biomarkers in clinical settings [2], although the use of C-reactive protein for widespread testing remains debatable [1]. In a number of general population, primary prevention and high-risk cohort studies, NT-proBNP has been shown to be strongly associated with risk of CVD and appears to have prognostic value over and above that of traditional risk factors [3][4][5][6][7][8][9]. However, the ability of NT-proBNP to predict cardiovascular events in specific conditions such as type 2 diabetes is less extensively studied.…”
Section: Introductionmentioning
confidence: 99%
“…PREVEND is a population-based prospective cohort study primarily aimed at investigating the natural course of increased levels of urinary albumin excretion (UAE) and its association with long-term renal and cardiovascular outcomes in the general population. Details of the design and methodology of the study have been published elsewhere [15][16][17][18]. In summary, in the period 1997-1998, all inhabitants of the city of Groningen, the Netherlands, aged 28-75 years were sent a one-page postal questionnaire and a vial to collect an early morning urine sample (n = 85,421).…”
Section: Study Populationmentioning
confidence: 99%